An Integrated Approach to Diabetic Retinopathy Research - Gardner, Thomas W. (2011)
This review discusses the pathophysiology of diabetic retinopathy related to direct effects of loss of insulin receptor action and metabolic dysregulation on the retina. The resulting sensory neuropathy can be diagnosed by structural and functional tests in patients with mild nonproliferative diabetic retinopathy. Research teams can collaborate to integrate ocular and systemic factors that impair vision and design strategies to maintain retinal function in persons with diabetes. Evolving concepts may lead to inclusion of tests of retinal function in the detection of diabetic retinopathy and neuroprotective strategies to preserve vision for persons with diabetes.